Mental health among single mothers in Cyprus: a cross-sectional descriptive correlational study - Elena Rousou; Christiana Kouta; Nicos Middleton; Maria Karanikola (BMC, 2019)
Abstract Background International literature reveals that single mothers experience increased levels of chronic stress, which is mainly due to economic hardship and reduced levels of social support. Eventually this leads to psychological distress. While most of the studies commonly identify that mental health disorders are common among single mothers compared to their married counterparts, the magnitude of the problem might be even larger since diagnosis-specific tools may mask important levels of distress of milder intensity. This study aims to assess the level of mental distress experienced by single mothers as measured by the GHQ-28, and how it is influenced by socioeconomic factors, as well as the level of perceived social support. Methods Between January and March 2012, Greek speaking single mothers who reside in Cyprus were recruited by either personal conduct through Single Mothers' Association (SMA), or by using snowball sampling technic. Mental distress was assessed with the General Health Questionnaire (GHQ-28) and perceived social support with the Social Provision Scale (SPS). All scales were completed anonymously and voluntarily by 316 single mothers. Univariable and multivariable associations with socio-demographic characteristics were investigated using chi-square tests and in multivariable backward stepwise logistic regression models respectively. Odds ratio of psychological distress across decreasing levels of social support were estimated in logistic regression models. . Results As many as 44.6% of the sample appeared to experience psychological distress (GHQ-28 total score ≥ 5). Strong associations with all health assessment tools were observed with variables relating to the lowest monthly family income, the presence of economic difficulties, the higher educational level, the age group 35-44 years and pre-existing illness. Social support as perceived by the mothers displayed a strong negative independent association with psychological distress, even after adjusting confounders. Conclusion This study highlights that single mothers are very likely to experience poor psychological well-being. With a steady rise in the proportion of single-parent families headed by a mother, these findings highlight a significant issue that would adversely affect many women and consequently their children and the community. It also emphasizes the necessity for interventions and strategies at community level in order to support this vulnerable population group.